KETURUNAN ARAB DI BUNGIN AYEB (TINAJAUN SOSIO-HISTORIS) - Fitriah; Endang Rochmiatun (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2025)
This study aims to examine the history of the formation of ethnicity in a remote area of South Sumatra, specifically in Tanjung Pasir Village, Pemulutan District, Ogan Ilir Regency. The background of this research is the limited number of academic studies addressing ethnic dynamics and the role of migrant communities in rural areas. The main issues discussed include the background of the emergence of the Arab ethnic group, patterns of social interaction with the local community, and the contributions of the Arab community to social, cultural, and religious life in Tanjung Pasir Village. This research employs a qualitative method with historical and sociological approaches. Data were collected through interviews, observation, and the study of relevant historical sources, and were analyzed using a descriptive-analytical approach. The findings indicate that the presence of the Arab ethnic group in Tanjung Pasir Village was closely linked to the role of religious figures who contributed to the spread of Islam. The process of assimilation, which occurred through social interaction and intermarriage with the local population, has resulted in the formation of a unique and harmonious community. The Arab-descendant community has made significant contributions to strengthening Islamic values, religious education, and the transmission of traditions and cultural practices that enrich local identity. These findings highlight the importance of interethnic interaction in rural areas in shaping cultural diversity and strengthening social cohesion within the community.